Dividend Dynamics: Exploring Liquidity’s Moderating Role in Indonesia’s Energy-Listed Companies - Rosiana, Rita; Wong, Wing Keung (International Journal of Economics and Financial Issues, 2024)
This paper investigates the potential reasons behind the inconsistencies in the factors that affect corporate dividend policy. In addition, it attempts to closely analyze the role of liquidity in the dynamics of these relationships and clarify the characteristics of the moderating variables involved. The analysis draws on financial and annual reports of a sample of publicly listed energy companies in Indonesia, utilizing moderating regression analysis as a methodological framework. This study encompasses 5 years of observations, from 2019 to 2023, and includes 60 firm-year observations across 12 companies. We find that neither profitability nor leverage significantly influences dividend policy, while asset tangibility demonstrates a negative impact. Furthermore, there is evidence that liquidity has a moderating effect on the relationships between both profitability and dividend payout and between leverage and dividend payout. However, liquidity variable does not have moderate impact on the association between asset tangibility and dividend policy. The findings emphasize the necessity of integrating asset tangibility and liquidity into the dividend payment strategies of listed energy companies in Indonesia. Proper management of these factors is essential to maintain sufficient liquidity for cash dividends and to facilitate corporate financing.